Gangliocytic paraganglioma of ampulla of Vater: Clinical case - Mesquita, Isabel; Peña, José Maria de la; Vilaça, Jaime; Davide, José; Daniel, Jorge; Graça, Luís; Teixeira, Manuel (Revista Portuguesa de Cirurgia; No 2 (2007): Setembro 2007 - II Série, 2007)
First described in 1962, Gangliocytic Paraganglioma (GP) is a rare tumor that has been increasingly reported in the lite- rature since then. It almost occurs in the second part of the duodenum, often at the Ampulla of Vater and the most common presenting sympton is, gastrointestinal bleeding. Its characteristic histologic appearance consists of a mixture of three types in varying proportion: epithelioid, spindled and ganglion cells. Almost reported cases of GP has followed a benign course however, regional lymph node metastasis has been reported. Transduodenal local resection is a good treatment for benign ampullary tumors and it can be accomplished with little morbidity and a low recurrence rate. Prolonged surveillance is indicated for local resections. Key-words: Gangliocytic Paraganglioma, Ampulla of Vater, Transduodenal local resection